Need for pharmacoeconomic consideration of antiepileptic drugs monotherapy treatment in persons with epilepsy - Sudhir C. Sarangi; Nivendeep Kaur; Manjari Tripathi (Elsevier, 2020)
Objective: Newer antiepileptic drugs (AEDs) are expected to have less adverse effects (AEs) and drug interactions as compared to conventional AEDs but the high cost is the major limitation for their use. This study evaluated variation in the cost of treatment with newer and conventional AEDs through its correlation with treatment efficacy and AEs in persons with epilepsy (PWE). Methods: This cross-sectional study included PWE (28.9 ± 9.9 years) having focal and generalized seizures on conventional [valproate, carbamazepine, phenytoin] or newer AEDs [levetiracetam, oxcarbazepine] for >6 months. Seizure frequency during the study (6 months) was compared to that within 6 months before the study. Other parameters assessed were Quality of life in epilepsy, Pittsburgh Sleep Quality Index, Gastrointestinal Quality of life Index, and Liverpool AEs Profile. The cost of treatment was determined as direct, indirect, and intangible costs. The incremental cost-effectiveness ratio (ICER) analysis was also performed. Results: Out of 214 PWE, 51.4% were on newer AEDs. Newer and conventional AEDs did not differ significantly in seizure frequency reduction (60.29 vs. 53.09%), quality of life parameters, though these were improved significantly during the study period. The direct medical cost and total cost of treatment were lesser with conventional AEDs (p < 0.001 in both) than newer AEDs, but the intangible cost did not differ. The total cost of treatment was significantly influenced by factors (as per regression analysis) including the type of AEDs (significant difference between valproate, carbamazepine, and levetiracetam), frequency of seizures, cost of medicine (70.34% of total cost), hospital admission, and treatment of AEs. As per ICER, newer AEDs need an additional USD 8.39 per unit reduction in seizure frequency. Conclusion: Newer AEDs have comparatively better efficacy, though not significant than conventional AEDs. However, the additional cost per unit improvement is quite high with newer AEDs, necessitating pharmacoeconomic consideration in epilepsy treatment.